2010
DOI: 10.21649/akemu.v15i1.23
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Surrogate Markers for Hepatitis B, Hepatitis C and HIV in Healthy Blood Donors at Shaikh Zayed Medical Complex, Lahore

Abstract: Introduction: This project was aimed to determine the seropositivity status for Hepatitis B surface antigen (HBsAg), antiHepatitis C (HCV) antibodies and antibodies to Human Immune Deficiency Virus (HIV) I and II in healthy blood donorsdonating blood at Shaikh Zayed Hospital Lahore.Material and Methods: The relevant data was collected during a period of 28 months from 1st January 2006 till 31st March2008. It was a cross sectional study which entailed screening of 60719 healthy donors. The donors were aged betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
0
4
3
Order By: Relevance
“…The prevalence of HBsAg Positive among general population donors in our study is also almost similar to reported for Punjab. However, prevalence among prisoner donors is high than reported for general population in our study and for Punjab (26,27,28,29). The prevalence of syphilis in our study among general population donors is half than reported by Shaukat Khanum Cancer Hospital, Lahore (only study which reported prevalence of syphilis among blood donors in Punjab) (11).…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…The prevalence of HBsAg Positive among general population donors in our study is also almost similar to reported for Punjab. However, prevalence among prisoner donors is high than reported for general population in our study and for Punjab (26,27,28,29). The prevalence of syphilis in our study among general population donors is half than reported by Shaukat Khanum Cancer Hospital, Lahore (only study which reported prevalence of syphilis among blood donors in Punjab) (11).…”
Section: Discussioncontrasting
confidence: 57%
“…The prevalence of HCV among general population donors in our study is almost similar to reported for Punjab. However, prevalence among prisoner donors is two to three times high than reported for general population in our study and for Punjab (26,27,28,29). The prevalence of HBsAg Positive among general population donors in our study is also almost similar to reported for Punjab.…”
Section: Discussioncontrasting
confidence: 55%
“…The data were from nine large cities of the country and 10 studies were conducted in the city of Karachi alone, 13,14,[17][18][19][20]38,40,42,45 while six and four were conducted in Lahore 25,28,30,36,37,44 and Peshawar, 22,39,41,43 respectively. ELISA was the predominant screening technology used in 27 studies; 13,14,[17][18][19][20]22,23,25,29,[32][33][34][35][36][37][38][39][40][41]42,45 one paper did not describe the methodology used, 31 while the remaining three studies were based exclusively either on immunochromatographic testing 24,30 or latex agglutination. 21 During 1988-2012, a total of 142 donors were reported to have HIV antibodies.…”
Section: Hiv Seroprevalence and Methodology Used In Blood Donorsmentioning
confidence: 99%
“…Fourteen reports described 285 208 sex-wise donations, including 258 628 male (90.7%) and 26 580 female (9.3%) donors. [18][19][20][21]23,27,28,[30][31][32]37,38,42,45 However, except for one study, 18 the HIV results were not delineated with respect to sex.…”
Section: Donor Sex and Hivmentioning
confidence: 99%
See 1 more Smart Citation